2018
DOI: 10.1371/journal.pone.0199985
|View full text |Cite
|
Sign up to set email alerts
|

Table tennis playing styles require specific energy systems demands

Abstract: The aim of the present study was to investigate the differences in energy system contributions and temporal variables between offensive and all-round playing styles. Fifteen male table tennis players (Offensive players: N = 7; All-round players: N = 8) participated in the study. Matches were monitored by a portable gas analyzer and the blood lactate responses was also measured. The contributions of the oxidative (WOXID), phosphagen (WPCr), and glycolytic (W[La]) energy systems were assumed as the oxygen consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 23 publications
2
26
0
9
Order By: Relevance
“…Table tennis is considered an aerobic dominant sport with the anaerobic alactic system playing a significant role during the rallies [10,12,37]. The findings from this study are consistent with the literature [9][10][11][12][13]37], wherein the percentage of energy contributions of E AER , E BLC , and E ALA range from 79.4-85.2%, 0.6-2.1%, and 12.9-20.0%, respectively, in this study (Table 2). However, in simulated matches, Zagatto et al found different percentages for E AER , E BLC , and E ALA of 96.5%, 1.0%, and 2.5%, respectively [10].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Table tennis is considered an aerobic dominant sport with the anaerobic alactic system playing a significant role during the rallies [10,12,37]. The findings from this study are consistent with the literature [9][10][11][12][13]37], wherein the percentage of energy contributions of E AER , E BLC , and E ALA range from 79.4-85.2%, 0.6-2.1%, and 12.9-20.0%, respectively, in this study (Table 2). However, in simulated matches, Zagatto et al found different percentages for E AER , E BLC , and E ALA of 96.5%, 1.0%, and 2.5%, respectively [10].…”
Section: Discussionsupporting
confidence: 87%
“…However, the contribution of each pathway is unclear for specific table tennis skills. Previous studies have explored the energetic profile of table tennis in training and simulated matches [9][10][11][12][13] with findings consistently showing an aerobic-dominant profile. However, the energetic profile in table tennis may be influenced by different physical loads placed on the players such as different footwork, stroke types, and stroke frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Three objectives of performance analysis are relevant to the study of young table tennis players. Technique analysis is concerned with the mechanical aspects of technique and how skills translate into performance [ 4 , 19 , 20 ]. Tactical analysis is concerned with strategies and tactical decisions that are manifested in a game [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three objectives of performance analysis are relevant to the study of young table tennis players. Technique analysis is concerned with the mechanical aspects of technique and how skills translate into performance [19,4,20].…”
Section: Introductionmentioning
confidence: 99%